"PENGAWAS BERKUALITAS, PEMILU BERINTEGRITAS" PERAN STRATEGIS BAWASLU DALAM MENJARING SDM PENGAWAS PEMILU AD HOC PROFESSIONAL DI KABUPATEN MUARO JAMBI. - Muhammad Hapis (JURNAL LEGISIA, 2022)
Bawaslu as a cooperative professional institution with integrity has a strategic role in Bawalu Muaro Jambi Regency in recruiting quality human resources. By supporting efforts to increase the capacity and integrity of supervisors by using stages in strategic management at the sub-district level to TPS which are Adhoc in nature, it includes three strategic steps. First, strategic planning using SWOT analysis. both scoring and grouping criteria based on recruitment problems and finally determining the choice of alternative strategies including, aggressive strategies, turn-around strategies, and defensive strategies that are projected according to the level of the problem